Sleep architecture, insulin resistance and the nasal cycle: Implications for positive airway pressure therapy - Catherine A.P. Crofts; Alister Neill; Angela Campbell; Jim Bartley; David E. White (Journal of Metabolic Health, 2018)
Background: The global pandemic of metabolic disease is worsening. The metabolic theory of obesity proposes that hormonal changes, especially hyperinsulinaemia, precede metabolic disease development. Although quality sleep is recognised as a key factor for good health, less is known about disrupted sleep as a risk factor for hyperinsulinaemia.